Patterns of Metacognitive Awareness Among Primary School Teachers - Palantis, N.John; Mohamed, Johan, A.; Ibrahim, A.S. Mohd; Ismail, S.H.; Anuar, N.K.; Ma’rof, A.M.; Buang, N. (Universitas Muhammadiyah Surakarta, 2017)
The purpose of this study is to identify level and patterns of metacognitive awareness among teachers in primary schools. This study focuses on aspects of declarative knowledge, procedural knowledge, conditional knowledge, planning, monitoring and evaluation of teachers. The study was descriptive in nature. A sample of 100 primary school teachers in Puchong, Selangor answered the Metacognitive Awareness Inventory for Teacher by Cem Balcikanli (2011). The data analysis was carried out using IBM Statistics version 24 to obtain descriptive measures. The results show that levels of metacognitive awareness among teachers are high at ninety three percent (93%). The results also show that there are no significant differences by gender, age, teaching experience, academic qualification and subject of teaching among primary school teachers. The metacognitive framework shows that metacognition knowledge and regulatory expertise were used by individuals to control their cognition. Teachers who have a higher level of metacognitive awareness can produce students with good academic achievement.